Effects of Multidimensional Treatment Foster Care on Psychotic Symptoms in Girls: RH = MTFC and Psychotic Symptoms - Poulton, Richie (J Am Acad Child Adolesc Psychiatry, 2014)
OBJECTIVE: Neurodevelopmental theories of psychosis highlight the potential benefits of early intervention, prevention, and/or preemption. How early intervention should take place has not been established, nor if interventions based on social learning principles can have preemptive effects. The objective was to test if a comprehensive psychosocial intervention can significantly alter psychotic symptom trajectories during adolescence – a period of heightened risk for a wide range of psychopathology. METHOD: This study was a randomized controlled trial (RCT) of Multidimensional Treatment Foster Care (MTFC) for delinquent adolescent girls. Assessment of psychotic symptoms took place at baseline and then 6, 12, 18, and 24 months post-baseline using a standardized self-report instrument (Brief Symptom Inventory). A second source of information about psychotic symptoms was obtained at baseline or 12 months, and again at 24 months using a structured diagnostic interview (the Diagnostic Interview Schedule for Children [DISC]). RESULTS: Significant benefits for MTFC over treatment-as-usual for psychosis symptoms were observed over a 24-month period. Findings were replicated across both measures. Effects were independent of substance use and initial symptom severity, and persisted beyond the initial intervention period. CONCLUSION: Ameliorating non-clinical psychotic symptoms trajectories beginning in early adolescence via a multifaceted psychosocial intervention is possible. Developmental research on non-clinical psychotic symptoms and their prognostic value should be complemented by more psychosocial intervention research aimed at modifying these symptom trajectories early in their natural history.